Gestão do conhecimento no planejamento de contratações de soluções em TI em Instituições Federais de Ensino Superior do Brasil: um diagnóstico usando análise envoltória de dados - Araújo, Beatriz Duarte Lima de (2016)
In the present social conjuncture, with fast transformations in all areas, is important that the knowledge and the business tactics work together in the organization. Federal institutions of higher education need a special view about the implantation and use of knowledge management, because of their peculiarities of teaching and governance. The acquisition planning of information technology lacks the support that woud enable a great improvement in the activities. This study has as general goal analyze the efficiency of IFES in Brazil concerning the knowledge management in information technology hiring, using for this purpose the method Data Envelopment Analysis (DEA), and Charnes, Cooper e Rhodes (CCR) model results-oriented. Moreover are presented the notion of KM, the leading theorists models about the theme, some types of diagnosis of KM related for public administration, as well as the notion of DEA. The study is the kind survey with quantitative approach. Regarding the goals is a descriptive research, applying a questionnaire based in the model created for Batista (2006). The questionnaire was applied to the managers of IT of 103 organizations of higher education in Brazil. Among the institutions to whom the questionnaire were sent, 86 responded. In the descriptive analysis are presented the results of the research showing the characterization of the IFES, like how the process hiring of technology solutions works, and how the initiatives of knowledge management are used to give suport to them. Among the 86 institutions analyzed according the Software Frontier Analyst, 57 were regarded efficient and 29 were regarded as not efficient. Are presented the benchmarkings, wich the inefficients IFES must consider for the improvement of their planning in IT, as well as they ought to evaluate the factors of entry and output analyzeds always with the goal of advance in the use of knowledge of management as suport for the hiring of IT solutions.